2019
DOI: 10.32479/irmm.8640
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Earnigs Volatility, Net Income and Comprehensive Income on Stock Prices on Banking Companies on the Indonesia Stock Exchange

Abstract: This paper aims to analyze the effect of earnings volatilty, net income and comprehensive income on stock prices on banking companies on the Indonesia Stock Exchange in the period of 2011 to 2016. This paper uses a quantitative approach by using secondary data consisting of 174 data of commercial banks on the Indonesia Stock Exchange, from 2011 to 2016 obtained from the Indonesia Stock Exchange website www.idx.co.id. and www.yahoofinance.com, The analysis technique used in this study is multiple linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…In general, it is believed that consumers shop not only about their needs but also to seek satisfaction in the shopping process (Babin et al, 2005), Pramita et al, 2020, Hadi et al, 2021, Woro et a.l, 2020. Consumer satisfaction is defined as happiness, satisfaction, and pleasure in getting service or service (Thaichon and Quach, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is believed that consumers shop not only about their needs but also to seek satisfaction in the shopping process (Babin et al, 2005), Pramita et al, 2020, Hadi et al, 2021, Woro et a.l, 2020. Consumer satisfaction is defined as happiness, satisfaction, and pleasure in getting service or service (Thaichon and Quach, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another study on the Iranian stock exchange (Dastgir & Velashani, 2008) could not confirm that comprehensive income is superior to net income for performance evaluation based on the stock returns, and could not find evidence that comprehensive income adjustments improve the ability to reflect firm performance. Rusdiyanto and Narsa (2019) in their research based on banking companies listed on the Indonesian stock exchange found no evidence of comprehensive income effects on stock prices.…”
Section: Literature Reviewmentioning
confidence: 94%
“…This study uses literature study method, namely data collection through secondary data sourced from the Central Bank, articles, and news in print and electronic media (Juanamasta et al, 2019;Prabowo et al, 2020;Rusdiyanto, Agustia, et al, 2020;Rusdiyanto, Hidayat, et al, 2020;Syafii et al, 2020), (Juanamasta et al, 2019), (R. Rusdiyanto & Narsa, 2019), (Gazali, Kusuma, Aina, Bustaram, Amar, et al, 2020), (Syafii et al, 2020), (Lamtiar et al, 2021), (Gazali, Kusuma, Aina, Bustaram, Risal, et al, 2020), (Rusdiyanto, Sawarjuwono, et al, 2020), (Shabbir et al, 2021), (Susanto et al, 2021), (Luwihono et al, 2021), (Rahayu et al, 2020), (Utari et al, 2020), (Prabowo et al, 2020), (Astanto et al, 2020), (H. T. , (Rusdiyanto, Sawarjuwono, et al, 2020), , (Rusdiyanto & Narsa, 2020), (Ulum et al, 2020), (R. Rusdiyanto et al, 2019), , , , (Hadi Susanto et al, 2021), (Woro Utari et al, 2020), (Susanto et al, 2021). The data and information are processed by the classification stage of the source and content of the news and the calsterization of the year of publication.…”
Section: Methodsmentioning
confidence: 99%